Women and Revolutionary Turmoil in the Middle East and North Africa - Mojtahedi, Elissa Rana (Glendon Journal of International Studies, 2015)
The recent revolutionary movements in the Middle East and North Africa have presented a unique opportunity for women to exert their influence in shaping the future of women’s rights. Specifically, the question arises as to whether social movements help women fight patriarchal structures in the Middle East. This paper has chosen the Green Movement in Iran as a focal point, using the rise of the Arab Spring in Egypt and Tunisia as a point of comparison. An extensive literature review was conducted to provide the historical context as well as an analysis of the rise of social movements. Using a transnational feminist lens, both cases were analyzed and it was found that neither the Arab Spring nor the Green Movement in Iran were able to facilitate the improvement of women’s rights. This was mainly found to be due to the traditional and patriarchal structures, and it is argued that for women to gain freedom and empowerment, Islam must be detached from the legal system. While the fight for women’s rights are seen as an uphill battle on an international level, Women and Revolutionary Turmoil in the Middle East and North Africa provides a relevant argument within the realm of international studies. Les mouvements révolutionnaires récents dans le Moyen-Orient et l’Afrique du Nord ont présenté une opportunité unique pour les femmes d’exercer leur influence afin de construire l’avenir des droits des femmes. Une question spécifique se pose à savoir si les mouvements sociaux aident les femmes à se battre contre les structures patriarcales ou non. Le point focal de cet essai est le mouvement de politique vert en Iran tandis que l’avènement du Printemps arabe en Égypte et en Tunisie est utilisé comme point de comparaison. Les deux cas ont été analysés à travers une lentille féministe transnationale et il en ressort qu’aucun mouvement n’a pu faciliter l’amélioration des droits des femmes. Plusieurs raisons expliquent cet échec, notamment les structures traditionnelles et patriarcales de ces régions. Cet essai fait aussi valoir que pour que les femmes puissent atteindre la liberté et l’autonomie, l’Islam doit être détaché du système légal. La lutte pour les droits des femmes est souvent considérée comme une lutte ardue au niveau international, et cet essai fournit un argument pertinent au sein des études internationales.